(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to explore the role of academic advisors in Saudi cultural missions in enhancing the quality of university education for scholarship students in light of digital transformation. The study adopted the descriptive analytical approach and developed a questionnaire comprising three dimensions: academic advisor duties, challenges faced, and the extent of digital technology utilization in academic advising. The instrument was administered to a purposive sample of 45 academic advisors working in three cultural missions (United States, United Kingdom, and Australia). Results revealed that academic advisors perform their duties at a high level, while facing organizational and technical challenges, most notably limited authority and administrative overload. The study also showed a relatively high level of digital tool adoption in academic monitoring. Based on the findings, a proposed framework was developed to activate the role of academic advisors, built upon four pillars: institutional empowerment, digital transformation, professional support, and performance indicators.